Cloud security using face recognition - Kumar S.; Sadhya D.; Singh D.; Singh S.K. (My University, 2025)
Establishing identity has become very difficult in the vastly crowded cloud computing environment. The need for a trustworthy cloud authentication phenomenon has increased in the wake of heightened concerns about authentication and rapid advancements in cloud computing, database access, and Internet communication. Face recognition is a non-intrusive method, and facial characteristics are probably most common biometrics features used by humans to identify others. Authentication for cloud computing using face recognition is based on security issues related to data access and cloud database in a cloud. It can provide a satisfactory level of security measures to users and service providers, cloud consumers, and different organizations. In this chapter, the authors cover different research aspects related to cloud security. © 2015, IGI Global.